Abscisic acid and other plant hormones: methods to visualize distribution and signaling - Waadt, Rainer; Hsu, Po-Kai; Schroeder, Julian I. (Bioessays, 2015)
The exploration of plant behavior on a cellular scale in a minimal invasive manner is key to understanding plant adaptations to their environment. Plant hormones regulate multiple aspects of growth and development and mediate environmental responses to ensure a successful life cycle. To monitor the dynamics of plant hormone actions in intact tissue, we need qualitative and quantitative tools with high temporal and spatial resolution. Here, we describe a set of biological instruments (reporters) for the analysis of the distribution and signaling of various plant hormones. Furthermore, we provide examples of their utility for gaining novel insights into plant hormone action with a deeper focus on the drought hormone abscisic acid.
Gesehen am 25.06.2020